It is a Glorious Cause and I Will Die for It - William Alves - Raible, Chris (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
This paper looks at one rather ordinary participant in the 1837 Rebellion in Upper Canada. William Alves was a young carpenter who, caught up in the turmoil of the time, eagerly volunteered and, consequently, suffered severely. Pieced together from many fragments—surviving family letters, assorted contemporary newspapers, hundreds of archived government documents, and various historical references, including the inscriptions on two little boxes—his story can here be told.